Peningkatan Efisiensi Pengelolaan SPP Siswa Berbasis Web dengan Pendekatan Metode Agile Development - Agus Tri Mulyadi; Rizky Meimaharani; Tutik Khotimah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
An efficient process for managing school fee payments is crucial for the operational sustainability of educational institutions. However, many educational institutions continue to face challenges with manual payment processes, including recording errors, delays in data management, and a lack of transparency for users. The objective of this research is to implement a web-based tuition management functionality using the Agile Development methodology. This approach allows for iterative software development to align with user needs effectively. The system being developed includes features for recording payments, transaction history management, automatic payment validation, and user notifications. The Agile Development methodology is employed with a flexible approach, enabling the gradual development of features through intensive collaboration with the school and its users. Implementation is carried out using the Laravel framework as a bootstrap for the backend and responsive interface design. Testing results demonstrate that the system enhances administrative process efficiency, minimizes recording errors, and provides easy access to payment data for both administrators and students. Specifically, the system reduces recording errors by up to 75% and improves administrative time efficiency by 40%. Moreover, it supports transparency through integrated real-time reporting. In summary, the web-based school fee management features developed with the Agile Development approach effectively meet the needs of educational institutions and provide a robust solution for managing school fee payments.